Itching in patients with chronic hand eczema: data from the CARPE registry - Ruppert, Linda M.; Apfelbacher, Christian; Molin, Sonja; Bauer, Andrea; Mahler, Vera; Schmitt, Jochen; Elsner, Peter; Diepgen, Thomas L.; Weisshaar, Elke (Dermatology, 2014)
Background: Itching is a leading symptom of chronic hand eczema (CHE) having a great impact on patients. The determinants of itching in CHE are unclear. Objective: We performed a cross-sectional analysis investigating factors associated with the presence and severity of itch in CHE patients from the CARPE registry. Methods: We present baseline data on itch in relationship with sociodemographic factors, severity of CHE, atopy, contact allergy, treatment and patient- reported outcomes including health-related quality of life (HRQoL). Results: Of 1,051 patients with CHE, 78.1% reported itching. Significant positive associations with itching were observed for younger age groups (17-25 and 26-45 years), for moderate, severe and very severe CHE and for small/moderate impairment in HRQoL. Atopic skin diathesis, hardly being able to realize treatment recommendations and very or extremely large impairments in HRQoL were associated with itch severity. Conclusion: Taking the identified variables into account may help identify vulnerable groups most affected by (severe) itch.
Gesehen am 20.10.2020